Modeling Services Liberalization : The Case of Tanzania - Jensen, Jesper; Rutherford, Thomas F.; Tarr, David G. (Washington, DC: World Bank, 2012)
This paper employs a 52-sector, small, open-economy computable general equilibrium model of the Tanzanian economy to assess the impact of the liberalization of regulatory barriers against foreign and domestic business service providers in Tanzania. The model incorporates productivity effects in both goods and services markets endogenously, through a Dixit-Stiglitz framework. It summarizes policy notes on the key business service sectors that were prepared for this work, and estimates the ad valorem equivalent of barriers to foreign direct investment based on these policy notes and detailed questionnaires completed by specialists in Tanzania. The authors estimate that Tanzania will gain about 5.3 percent of the value of Tanzanian consumption in the medium run (or about 4.8 percent of gross domestic product) from a full reform package that also includes uniform tariffs. The estimated gains increase to about 16 percent of consumption in the long-run, steady-state model, where the impact on the accumulation of capital from an improvement in the productivity of capital is taken into account. Decomposition exercises reveal that the largest gains to Tanzania will derive from liberalization of costly regulatory barriers that are non-discriminatory in their impacts between Tanzanian and multinational service providers.